The endocannabinoid N-arachidonoyl dopamine (NADA) selectively induces oxidative stress-mediated cell death in hepatic stellate cells but not in hepatocytes - Wojtalla, Alexandra; Herweck, Frank; Singer, Manfred V.; Siegmund, Sören Volker (American journal of physiology. Gastrointestinal and liver physiology, 2012)
The endocannabinoid system is a crucial regulator of hepatic fibrogenesis. We have previously shown that the endocannabinoid anandamide (AEA) is a lipid mediator that blocks proliferation and induces death in hepatic stellate cells (HSCs), the main fibrogenic cell type in the liver, but not in hepatocytes. However, the effects of other endocannabinoids such as N-arachidonoyl dopamine (NADA) have not yet been investigated. The NADA-synthesizing enzyme tyrosine hydroxylase was mainly expressed in sympathetic neurons in portal tracts. Its expression pattern stayed unchanged in normal or fibrotic liver. NADA dose dependently induced cell death in culture-activated primary murine or human HSCs after 2-4 h, starting from 5 μM. Despite caspase 3 cleavage, NADA-mediated cell death showed typical features of necrosis, including ATP depletion. Although the cannabinoid receptors CB1, CB2, or transient receptor potential cation channel subfamily V, member 1 were expressed in HSCs, their pharmacological or genetic blockade failed to inhibit NADA-mediated death, indicating a cannabinoid-receptor-independent mechanism. Interestingly, membrane cholesterol depletion with methyl-β-cyclodextrin inhibited AEA- but not NADA-induced death. NADA significantly induced reactive oxygen species formation in HSCs. The antioxidant glutathione (GSH) significantly decreased NADA-induced cell death. Similar to AEA, primary hepatocytes were highly resistant against NADA-induced death. Resistance to NADA in hepatocytes was due to high levels of GSH, since GSH depletion significantly increased NADA-induced death. Moreover, high expression of the AEA-degrading enzyme fatty acid amide hydrolase (FAAH) in hepatocytes also conferred resistance towards NADA-induced death, since pharmacological or genetic FAAH inhibition significantly augmented hepatocyte death. Thus the selective induction of cell death in HSCs proposes NADA as a novel antifibrogenic mediator.